The rights of children and young people under special educational needs legislation in England: an inclusive agenda?. Issue 5 (4th May 2019) - Harris, Neville; Davidge, Gail
ABSTRACT: In this article we consider the rights of children and young people with special educational needs and disabilities in England, introduced under the Children and Families Act 2014, within the context of the wider reforms made by the Act. Drawing primarily on key informant interviews conducted as part of an ESRC project on Autonomy, Rights and Children with Special Needs: A New Paradigm? (ES/P002641/1), and making reference to the international framework of children's and disabled persons' rights, we present an analysis of the (mostly professional) viewpoints gathered and what they tell us about the progress towards the realisation of children and young people's autonomy and agency in this field.